O diálogo entre cortes e o novo paradigma para o juiz brasileiro: o controle difuso de convencionalidade - Figueiredo, Sylvia Marlene de Castro (2017)
The present study focuses on the dialogue between courts with a special focus on the interpretive activity by the applicator of the law. It addresses the dialogue between cuts and the control of conventionality. It studies the interdisciplinarity between constitutional law and international law. It examines the concept of sovereignty, which must be understood and managed as a relative concept. It demonstrates that constitutional pluralism is demanding from the constitutional interpreter the dialogue between courts, mainly through the diffuse control of conventionality, which has been and should be used, as a general rule, by Brazilian judges. The issue under discussion is of great importance because it inaugurates a new stage of constitutional interpretation and because the universal claim to the protection of human rights is the main theoretical basis for the practice of transnational dialogue, coupled with the differentiated status of international human rights treaties and the similarity Between the object of protection of the norms of human rights and the protective norms of domestic law. In this way, there is a system with multiple levels of protection, in which the maxim of the primacy of the norm more favorable to the human being prevails. In addition, the interpretive's argumentative activity, during the constitutional interpretation, has the power to carry out effective legal-discursive integration